Trends in Resource Utilization Associated with the Inpatient Treatment of Neonatal Congenital Heart Disease. (5th June 2013) - Smith, Andrew H.; Gay, James C.; Patel, Neal R.
Abstract Introduction While neonates account for a significant proportion of health care expenditures related to inpatient care for congenital heart disease, key drivers of resource utilization among this population are poorly defined. Methods Data from 2005 through 2011 were extracted from the Pediatric Health Information System for patients assigned a discharge All Patient Refined Diagnosis Related Group of 630 (neonates with birthweight >2499 g undergoing a major cardiovascular procedure). Mortality risk adjustment for patients undergoing operative interventions was performed with the Risk Adjusment in Congenital Heart Surgery (RACHS‐1) score. Results A total of 13 156 cases were included in the analysis. Despite only a 3% increase in case mix index and no significant change in operative acuity over the study period (RACHS classifications of 3 or greater 67% in 2005 vs. 66% in 2011, P = .64), there were inflation‐adjusted increases in both total estimated cost per case of (50% to 151 760 in 2011, P < .001), and mean charge per case (33% to 433 875 in 2011, P < .001). Pharmacy charges increased by 16% (P < .001), with agents including chlorothiazide and albumin accounting for the highest patient charges over the study period. Imaging charges increased by 42% (P < .001), with an average of 5.7 echocardiograms and 6517 in associated charges per case by 2011. While the proportion of patients receiving nitric oxide remained consistent, mean duration of administration increased by 25% to 6.6 days by 2011, accounting for average charges of 52 141 per patient exposed. Conclusions Among neonates with serious congenital heart disease, increases in both institutional costs and charges to the patient are associated with relatively consistent utilization practices in recent years. Multiinstitutional collaboration may prove useful in aligning evidence‐based reductions in practice variation with limitations in resource utilization without compromising the quality of care.